Efektivitas Model Peer Education terhadap Tingkat Pengetahuan Ibu Bayi Tentang Praktik Female Genital Mutilation di Desa Sei Suka Deras Kecamatn Sei Suka Kabupaten Batubara Tahun 2024 - Ariska Fauzianty; Nova Isabella Mariance Br Napitupulu; Sri Ningsih; Lasria Yolivia; Khairunnisa Khairunnisa; Humaida Hanim; Plora Novita (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Globally, at least 100 million girls are at risk of female circumcision each year or almost 6,000 children every day. Female circumcision in Indonesia is generally based on traditions or cultures that are passed down from generation to generation. This study aims to determine the effectiveness of the Peer Education Model on the level of knowledge of mothers and babies about the practice of Female Genital Mutilation. The research method is Quasi Experiment with one group pretest and posttest without control design. The sample size is 50 people according to the inclusion criteria. data with the T statistical test (paired t test). Research results The level of knowledge of the intervention group before the intervention Most have poor knowledge of 12 respondents (48%) and After the intervention, almost Most have good knowledge of 17 respondents (68%). The level of knowledge of the control group before the intervention Most have poor knowledge of 14 respondents (56%) and after the intervention Most have poor knowledge of 14 respondents (56%). It is expected that health workers provide health education and always carry out monitoring and evaluation at the Health Center or other health service centers to conduct continuous home visits.